2015
DOI: 10.1111/brv.12232
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity selection theory: concepts and evidence

Abstract: Fitness results from an optimal balance between survival, mating success and fecundity. The interactions between these three components of fitness vary depending on the selective context, from positive covariation between them, to antagonistic pleiotropic relationships when fitness increases in one reduce the fitness of others. Therefore, elucidating the routes through which selection shapes life history and phenotypic adaptations via these fitness components is of primary significance to understanding ecologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 234 publications
(465 reference statements)
6
137
1
Order By: Relevance
“…Alternatively, the variation in body size might result from faster growth rates of one of the sexes, or individuals of one sex might grow for a longer time F I G U R E 5 Linear regression between log (male body size) on log (female body size) in plateau zokors (a) and that of plateau zokors with eight other zokor species (b) F I G U R E 6 Linear regression between log (litter size) on log (female body size) in females (a) and distribution of testicle size to body size in males (b) plateau zokors than the opposite sex (Blanckenhorn et al, 2007). Our results revealed that different age-groups showed alterations in different morphological traits mainly owing to the growth and maturation of animals that might also reflect the different habits between males and females for the ingestion of diverse food items for heat production in cold climates in addition to other physiological regulators of food intake (Patterson & Abizaid, 2013). The bigger morphological traits in males in group I during the initial stages of development validate the assumption that SSD starts as early as possible, which supports the body for further growth and development as age advances (Le Galliard, Massot, Landys, Meylan, & Clobert, 2006).…”
Section: Development Of Different Morphological Traits During Agingmentioning
confidence: 73%
See 1 more Smart Citation
“…Alternatively, the variation in body size might result from faster growth rates of one of the sexes, or individuals of one sex might grow for a longer time F I G U R E 5 Linear regression between log (male body size) on log (female body size) in plateau zokors (a) and that of plateau zokors with eight other zokor species (b) F I G U R E 6 Linear regression between log (litter size) on log (female body size) in females (a) and distribution of testicle size to body size in males (b) plateau zokors than the opposite sex (Blanckenhorn et al, 2007). Our results revealed that different age-groups showed alterations in different morphological traits mainly owing to the growth and maturation of animals that might also reflect the different habits between males and females for the ingestion of diverse food items for heat production in cold climates in addition to other physiological regulators of food intake (Patterson & Abizaid, 2013). The bigger morphological traits in males in group I during the initial stages of development validate the assumption that SSD starts as early as possible, which supports the body for further growth and development as age advances (Le Galliard, Massot, Landys, Meylan, & Clobert, 2006).…”
Section: Development Of Different Morphological Traits During Agingmentioning
confidence: 73%
“…The sexual selection hypothesis (Blanckenhorn et al, 2007) predicts that larger males might compete more efficiently to gain access to mates for better reproductive success and this drives MBSSD (Stillwell, Blanckenhorn, Teder, Davidowitz, & Fox, 2010). The fecundity selection theory states that larger females would produce higher numbers of healthier offspring and/ or reproduce more frequently than smaller ones, thereby driving FBSSD or "reversed" sexual size dimorphism (Pincheira-Donoso & Hunt, 2017). An alternative, sex-based ecological divergence (Brown, Madsen, & Shine, 2017) hypothesis states that SSD evolves to facilitate different sexes to exploit the available resources differently to reduce competition between them (Szekely, Reynolds, & Figuerola, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, spiders are one of the few groups that exhibit ISWs in which males are not larger than females. Female-biased sexual size dimorphism, prevalent in invertebrates and ectothermic vertebrates (but also occurring in endotherms; Ralls, 1976), is probably a result of fecundity selection (Darwin, 1871;Andersson, 1994;Pincheira-Donoso & Hunt, 2017). In spiders, an additional selective factor that keeps males smaller than females is related to enhanced dispersal abilities of males while searching for mates (Corcobado et al, 2010).…”
Section: (8) Additional Selective Pressures On Iswsmentioning
confidence: 99%
“…In this review, we follow the traditional division of sexually dimorphic traits in three groups: primary, secondary, and ecological sex traits (Darwin, 1871;Andersson, 1994;Williams & Carroll, 2009); yet we highlight the necessity of an in-depth discussion of this classification taking into account fecundity selection (review in Pincheira-Donoso & Hunt, 2017), social competition (West-Eberhard, 1983), and sexual differences in offspring care or other behaviours associated with reproduction (e.g. Cade & Maclean, 1967;Wilson et al, 2003;Ponssa & Barrionuevo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…21] . Rensch's rule may be explained by sexual selection and fecundity selection [22][23][24][25][26][27][28][29] . The macro-evolutionary pattern is unresolved in Diplopoda [30] .…”
Section: Introductionmentioning
confidence: 99%